2019
DOI: 10.1109/jiot.2019.2904802
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Modeling and Experimental Validation of NB-IoT Device Energy Consumption

Abstract: The recent standardization of 3GPP Narrowband Internet of Things (NB-IoT) paves the way to support Low-Power Wide-Area (LPWA) use cases in cellular networks. Narrowband IoT (NB-IoT) design goals are extended coverage, low power and low cost devices, and massive connections. As a new radio access technology, it is necessary to analyze the possibilities NB-IoT provides to support different traffic and coverage needs. In this paper, we propose and validate an NB-IoT energy consumption model. The analytical model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 9 publications
(13 reference statements)
1
38
0
1
Order By: Relevance
“…To assess energy consumption of the EPMD, a simplified energy consumption model is employed, which was derived from multiple sources on the calculation of GPRS [ 73 ], NB-IoT [ 22 , 74 , 75 ], LoRaWAN [ 22 , 76 , 77 , 78 ] and Sigfox [ 22 , 79 ] energy consumption. Simplifications are based on operational experience with the EPMD and recent publications including analysis and field testing of LPWAN sensors and monitoring devices [ 13 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…To assess energy consumption of the EPMD, a simplified energy consumption model is employed, which was derived from multiple sources on the calculation of GPRS [ 73 ], NB-IoT [ 22 , 74 , 75 ], LoRaWAN [ 22 , 76 , 77 , 78 ] and Sigfox [ 22 , 79 ] energy consumption. Simplifications are based on operational experience with the EPMD and recent publications including analysis and field testing of LPWAN sensors and monitoring devices [ 13 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Several works have evaluated NB-IoT technology in terms of its UE's power consumption analysis and battery life-time estimations [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] that can be categorized into analytical, simulations, and experimental measurements based analysis. Most of these works provide analytical models with simulation based energy estimations [6]- [14].…”
Section: A State Of the Artmentioning
confidence: 99%
“…The authors in [8] have presented an NB-IoT energy consumption model with uplink and downlink data transmissions as defined by Poisson processes. The authors in [9] and [10] have tried to estimate the NB-IoT device battery life-time by using some simplified energy consumption equations, whereas the authors in [12] have proposed an NB-IoT UE energy consumption analytical model based on Markov chains. Similarly, the work in [14] presents an analytical model for evaluating the latency and maximum number of devices in any network.…”
Section: A State Of the Artmentioning
confidence: 99%
“…Regarding NB-IoT energy management, 3GPP introduced two power saving schemes in Releases 13 and 14, i.e., PSM and eDRX. These modes allow the UE to enter a state where monitoring the signaling and scheduling information is not needed [43]. There is already research available on the energy performance of NB-IoT with regard to this.…”
Section: Performance Analysis With Real Devicesmentioning
confidence: 99%
“…The results show that a device transmitting 100 bytes of payload every 24 h can operate for more than 12 years with a C-cell battery. The authors of [43] presented and validated a model of NB-IoT performance with regard to battery lifetime and latency. The results indicated that power does not grow in a linear manner in terms of packet length; instead, it is worsened due to the segmentation of longer packets.…”
Section: Performance Analysis With Real Devicesmentioning
confidence: 99%